Dinoflagellates of the Crimean Peninsula and its coastal waters - Bryantseva, Yu.V. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2020)
The article is devoted to the generalization of the existing information concerning dinoflagellates of the Crimea. A list of dinoflagellate species of continental waters of the peninsula and the Crimean coast (Black and Azov seas) of Ukraine was compiled. It is based on the analysis of literature and original data obtained in 1987, 1992-1993 and 2011 in the Black Sea. The list of dinoflagellata species of Crimea includes 196 species (206 infraspecific taxa) belonging to 64 genera, 36 families, 15 orders and 3 classes. Eighteen species have been recorded in the fresh and salt water bodies and mud volcanoes of the least studied continental part of Crimea; half of them were also found in marine waters. Dinoflagellates of the Azov coast of Crimea and the Kerch Strait are similar in number of species, but differ significantly in composition (26 and 31 species, respectively; only 13 (25%) of them are common). The greatest number of species of dinoflagellates found on the Black Sea coast of Crimea. It is almost half of all species known for the Black Sea (196 and 447, respectively). To compare the species richness of dinoflagellates from different regions of the Crimea, survey data covering all areas in a short period of time are of great importance. A total of 74 species of dinoflagellates belonging to 3 classes, 11 orders, 22 families and 30 genera were found off the coast of Crimea. The most species-rich genera are Protoperidinium Bergh (17), Dinophysis Ehrenb. (8), Gymnodinium F.Stein (7) and Prorocentrum Ehrenb. (6). Based on the analysis of original and literature data and the criterion of similarity of the species composition of Crimean dinoflagellates, it’s division into five algofloristic regions is proposed: the western Black Sea coast of Crimea (from Karkinitsky Bay to Cape Aya); southeastern (from Ayia to Takil), Kerch Strait, Azov coast of Crimea and land (which, in turn, is divided into steppe and mountainous Crimean regions). It is in compliance with the algofloristic zoning of Ukraine.